2021
DOI: 10.1016/j.omtn.2020.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing cardiac reprogramming via synthetic RNA oligonucleotides

Abstract: Reprogramming scar fibroblasts into new heart muscle cells has the potential to restore function to the injured heart. However, the effectiveness of reprogramming is notably low. We have recently demonstrated that the effectiveness of reprogramming fibroblasts into heart muscle cells (cardiomyocytes) is increased by the addition of RNA-sensing receptor ligands. Clinical use of these ligands is problematic due to their ability to induce adverse inflammatory events. To overcome this issue, we sought to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Since our initial discovery, we have gone on to demonstrate that miR combo improves cardiac function in heart injury models ( 5 ). Moreover, we have also found that reprogramming via miR combo utilizes immunity and epigenetic pathways ( 6 , 7 ). In addition to reprogramming fibroblasts to cardiomyocytes, miRNAs have also been used to reprogram cells to pluripotency ( 8 ) as well as to neurons ( 9 ).…”
mentioning
confidence: 84%
“…Since our initial discovery, we have gone on to demonstrate that miR combo improves cardiac function in heart injury models ( 5 ). Moreover, we have also found that reprogramming via miR combo utilizes immunity and epigenetic pathways ( 6 , 7 ). In addition to reprogramming fibroblasts to cardiomyocytes, miRNAs have also been used to reprogram cells to pluripotency ( 8 ) as well as to neurons ( 9 ).…”
mentioning
confidence: 84%
“…Upon binding to their specific ligands, RNA-sensing receptors activate a common signaling pathway that includes the transcription factors activator protein 1, interferon regulatory factors 3/7, and nuclear factor kappa B (NFkB) ( 79 ), which is consistent with observations that pharmacological TLR3 activators strongly enhance, while inhibitors of the TLR3-NFkB pathway block, the maturity of miR-combo–reprogrammed CMs ( 80 ). Synthetic RNA agonists of Rig-1 also enhanced the yield of mature CMs in response to treatment with miR-combo ( 81 ). Interestingly, miR-133 enhanced MEF2C, GATA4, and TBX5-induced direct cardiac reprogramming in human fibroblasts via targeting immune-related genes ( 82 ), suggesting distinct mechanisms underlying mouse and human reprogramming.…”
Section: Direct Reprogramming Of Cfs Into Cmsmentioning
confidence: 99%
“…Hu et al. observed that a stabilized RNA, ICR2, increased the level of cardiomyocyte-specific genes in reprogrammed “fibroblasts” and enhanced their ability to differentiate into cardiomyocytes via the RIG-I and TLR3 pathways ( 78 ). In addition to the discrepancy in the above findings, the role of RIG-I in cell senescence is also controversial.…”
Section: The Activation Of Rig-imentioning
confidence: 99%
“…This suggests the inflammatory function of RIG-I in the progression of dilated cardiomyopathy. Another study showed that ICR2 (a stabilized RNA) enhanced the ability of cardiac fibroblasts to reprogram into cardiomyocytes via the RIG-I pathway without inducing inflammatory events ( 78 ). These results reveal the controversial role of RIG-I in cardiac dysfunction caused by different stimuli and requires further research to validate the phenotypes and underlying mechanisms.…”
Section: The Activation Of Rig-imentioning
confidence: 99%